RELATING LIGHT REFLECTANCE OF A LEAF TO LIGHT ABSORBANCE BY FOLIAR CHLOROPHYLL AS A PRELIMINARY APPROACH TO DETECTION OF FOREST CONDITION BY REMOTE SENSING - Eun-A Cho; Je-Young Lee; Sun-Gu Lee; Gab-Sue Jang (Journal of Animal and Plant Sciences, 2016)
A trial for estimating leaf chlorophyll content based on leaf reflectance was conducted for three major plant species in Daegu, South Korea. To estimate the chlorophyll content in a leaf, we measured the leaf elongation and related the leaf reflectance to its absorbance. Leaves of the target species were found to start elongating around the middle of April and continued elongation until the middle of May, indicating that April and May in South Korea are the proper period to detect differences in leaf size. Reflectance increased progressively from the first survey date (April 14) to the last survey date (May 16); however, the reflectance became saturated on May 10. There was the possibility to detect within-species and/or among-species variations with temporal changes in leaf reflectance, especially at NIR (near infrared) ranges during the leaf-growing period. Absorbance by a leaf and its trend during the leaf-growing period tended to be contrary to leaf reflectance, and gradually increased with leaf elongation. The chlorophyll content was shown to increase gradually and continuously, regardless of trends in leaf reflectance. Correlation maps combining the NIR range with wavelengths other than blue for NDVI (normalized difference vegetation index) were shown to explain the chlorophyll content quite well.
Keywords: Leaf reflectance; Leaf absorbance; Chlorophyll content; Vegetation index; Correlation map